Concept of Mental Education: A Perspective of Ibn Qayyim Al-Jawziyyah - Makmudi Makmudi (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2021)
Man consists of two elements, namely body and spirit, so that human beings are jasiman and ruhiyah at once. Hummans are also part of one element of the elements that exist in an educational process. Three element include the soul, the mind, the heart, and the human body. Humman and education, can not be separated from each other. Both are an interconnected entity, human as the perpetrator and education as a syistem in the process to achieve the goal of education itself. Mental health education requires alignment and harmony in various stages and sectors as well as attention to the three elements that exist in the human self that is the physical element (psychomotor) which includes body building, skill (skill) and sexual education, the spiritual element (affective) which includes the formation of faith, and iradah (the will), the element of reason (cognitive) which includes the coaching of intelligence and the provision of knowledge. The purpose of writing this research is to know and analyze thoughts about the concept of life education perspective Ibn Qayyim al-Jauziyyah. Soul education is considered successful, if one's soul has reached the degree of nafs muthmainnah, which has three main characteristics that mutually reinforce one another, namely; (1) a faithful soul to God, (2) a patient soul, (3) a soul that is self-serving to Allah (tawakal). Through the process of mental education which includes: the foundation of theology, the purpose of mental education, integrated curriculum / manhaj at-takamul, appropriate methods and applicable according to its stages, such as: takhliyah stages, tahliyah stages, muhasabah an-nafs, dzikrullah, and tahqiq 'ubudiyah. So that from the process will give birth ihsan attitude, and will increase the piety in worship, both related to God and those related to humans and the surrounding natural environment. Because, the essence of ihsan attitude itself is upholding 'ubudiyah.